Pediatric Teleradiology in Low-Income Settings and the Areas for Future Research in Teleradiology - Andronikou, Savvas (Frontiers in Public Health, 2014)
Teleradiology is an established mechanism to overcome the lack of on-site radiologists and can benefit children in developing countries. In this “perspective” on teleradiology for pediatric care in underdeveloped countries, three low-cost teleradiology programs are discussed from experiences of one teleradiologist, in relation to previous publications on this subject. Key issues discussed include mechanisms for sustainability, cost-effectiveness, resources, and barriers to success. Reliance on each link of a telereading chain is highlighted as a constant source for concern.